Stres pada Mahasiswa STT Cipanas: Perbandingan antara Pembelajaran Tatap Muka dan Daring - Martin Elvis; Dennie Olden Frans; Gustaf Redolof Yahya Rame (The New Perspective in Theology and Religious Studies, 2022)
AbstractIn dealing with the impact of the COVID-19 pandemic, Cipanas Theological Seminary students must adapt to changes in the Distance Learning process. This has an impact on student academic stress. The study was conducted on 43 (semester 3 and semester 5) students of STT Cipanas as participants to see the difference in academic stress levels between students who have studied face-to-face with students who take distance learning. To obtain data on differences in stress levels between face-to-face lectures and distance learning, researchers used the Academic Stress Scale measuring instrument which has been translated in Awaludin's research (2015). This instrument has been modified by Setiadi, et al (2020). With the analysis technique of Independent Samples T-Test and Paired Sample T-Test. 1) The academic stress level of 3rd semester students during distance learning is significantly higher than 5th semester. 2) The level of academic stress of 5th semester students during distance learning is significantly higher than face-to-face learning. Although the COVID-19 pandemic is not certain to be completed in a short time, the institution can use the results of this research to develop learning designs that minimize academic stress on students in distance learning.